ANALISIS BUTIR SOAL HOTS (HIGH ORDER THINKING SKILL) PADA SOAL UJIAN SEKOLAH KELAS XII MATA PELAJARAN BAHASA INDONESIA DI SMK AN-NAHL - Tari Wulandani; Ayu Cendra Kasih; Latifah Latifah (IKIP Siliwangi, 2019)
Developing evaluation tools for student learning outcomes is a task that must be developed by the teacher. The aim is to find out the success of achieving the learning objectives that have been formulated. In the 2013 curriculum, evaluation tools or questions that are arranged must be able to stimulate students' thinking abilities. Therefore, the development criteria for HOTS or high-level thinking skills are applied. In compiling the HOTS problem the teacher can use a cognitive Operational Verb (KKO) in Bloom's Taxonomy. The cognitive domain consists of the simplest to the most complicated. The cognitive level is divided into two, namely LOTS (Low Order Thinking Skills) and HOTS. The LOTS category is at the remembering level (C1), understands (C2), and applies (C3). While the HOTS category is at the level of analyzing (C4), evaluating (C5), and creating (C6). The research conducted is, of course, to find out how many items are included in the LOTS and HOTS criteria of the X-class AN-NAHL Vocational School Exam questions. In the research qualitative methods are used where the results of the research will be described. From the results of the analysis, there were 22.2% of LOTS questions consisting of 0% level (C1), 8.9% understanding level (C2), and 13.3% with applying level (C3). Then for the HOTS category, there were 77.8% consisting of 66.7% analyzing level (C4), 6.7% evaluating level (C5) and 4.4% creating level (C6).